Darwin Koenig letter to Nicholas S. Halmi regarding spring bird sightings, June 4, 1979 - Koenig, Darwinet al (1979)
Letter from Darwin Koenig to Nicholas S. Halmi regarding spring bird sightings from various locations, June 4, 1979. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1979. Epson - sheet feed/flatbed